A Phenomenographic Study of Lecturers’ Conceptions of Teaching and Learning and their Approaches to Teaching - Sari Ahmed, Anissa Fizya (International Journal For Research In Educational Studies, 2019)
The present study aims at investigating lecturers’ conceptions of teaching and learning, the approaches to teaching they adopt, and the correlation between the conceptions and approaches identified. It was carried out with fourteen Algerian lecturers at the department of English and uses a phenomenographic method of data collection and analysis. The results reveal that the lecturers hold five conceptions of teaching and learning and adopt five approaches to teaching. A strong correlation between lecturers’ conceptions of teaching and learning and the approaches they adopt was found. It was suggested to integrate a conceptual change approach into teacher development programs.